Archaeological and Strategic Study of the Forts and Strongholds of Medieval Jharkhand : मध्यकालीन झारखंड के किलों एवं दुर्गों का पुरातात्विक एवं सामरिक अध्ययन - Singh, Digvijay (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The forts and strongholds of medieval Jharkhand (16th–18th century) present significant evidence of regional power, architectural skill, and strategic foresight. Forts such as Palamu, Navratnagarh, Shahpur Chandni, Ramgarh, and Porahat, built by the Chero and Nagvanshi rulers, were not only strong from a military perspective but also functioned as administrative and cultural centers. These forts were constructed at naturally secure locations—such as high hills, dense forests, and riverbanks—which made their defense capability and surveillance system highly effective. Archaeological evidence indicates that these forts were built using stone, lime, and surkhi, with strong ramparts, bastions, arched gateways, and developed water-management systems. The multi-storied structure and water-gate system of Navratnagarh, and the Mughal architectural influence seen in Palamu Fort, reflect the technological advancement and cultural synthesis of this period. From a strategic point of view, these forts had features such as multi-layered security, limited entry gates, moats, and secret passages, which made them self-sufficient during times of siege. Abstract in Hindi Language: मध्यकालीन झारखंड (16वीं-18वीं शताब्दी) के किले एवं दुर्ग क्षेत्रीय सत्ता, स्थापत्य कौशल और सामरिक दूरदर्शिता के महत्वपूर्ण प्रमाण प्रस्तुत करते हैं। चेरो और नागवंशी शासकों द्वारा निर्मित पलामू, नवरत्नगढ़, शाहपुर चाँदनी, रामगढ़ तथा पोराहाट जैसे किले न केवल सैन्य दृष्टि से सुदृढ़ थे, बल्कि प्रशासनिक और सांस्कृतिक केंद्रों के रूप में भी कार्य करते थे। इन किलों का निर्माण प्राकृतिक रूप से सुरक्षित सीलों जैसे ऊँची पहाड़ियों, घने वनों और नदी तटों पर किया गया, जिससे उनकी रक्षा क्षमता और निगरानी प्रणाली अत्यंत प्रभावी बनी। पुरातात्विक साक्ष्यों से ज्ञात होता है कि इन किलों में पत्थर, चूना और सुर्खी का उपयोग कर मजबूत प्राचीरें, बुर्ज, मेहराबदार द्वार तथा जल-प्रबंधन तंत्र विकसित किए गए थे। नवरत्नगढ़ की बहुमंजिला संरचना और जल-द्वार प्रणाली तथा पलामू किले में मुगल स्थापत्य प्रभाव इस युग की तकनीकी उन्नति और सांस्कृतिक समन्वय को दर्शाते हैं। सामरिक दृष्टि से, इन किलों में बहुस्तरीय सुरक्षा, सीमित प्रवेश द्वार, खाइयाँ और गुप्त मार्ग जैसी विशेषताएँ विद्यमान थीं, जो उन्हें घेराबंदी के समय आत्मनिर्भर बनाती थीं। Keywords: मध्यकालीन झारखंड, किले एवं दुर्ग, चेरो वंश, नागवंशी शासक, पलामू किला, नवरत्नगढ़, पुरातत्व, सामरिक विश्लेषण, स्थापत्य शैली, जल-प्रबंधन